Agricultural diversification in the Caribbean community : some issues - Demas, William G. (CDB BridgetownBB, 1987)
Briefly discusses the agricultural situation in CARICOM and the ability to produce and willingness to consume more local and regional food. Defines and highlights the benefits of agricultural diversification discussing costs that would be incurred mainly in the area of research. Outlines the reasons for limited progress in agricultural diversification and gives guidelines for future agricultural development. Appendices contain a list of diversification products of sugar-cane and discuss the use of sugar-cane as livestock feed.